2021
DOI: 10.1002/lio2.685
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of celecoxib and acetaminophen for pain relief in pediatric day case tonsillectomy: A randomized double‐blind study

Abstract: Objective Post‐tonsillectomy pain is a common morbidity in children. The aim of this study was to compare the efficacy of celecoxib with acetaminophen on pain relief in pediatric day‐case tonsillectomy. Methods We compared the analgesic effect of celecoxib (99 patients) with acetaminophen (100 patients) for the management of post‐tonsillectomy pain. Post‐tonsillectomy pain score was evaluated three times a day for 7 days. In addition, the incidence of post‐tonsillectomy bleeding and the rate of patients who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Full‐text review of these 624 articles was conducted and a total of 71 articles were selected for inclusion (Figure 1). 5,6,8,16‐82 Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Figure 2A and B). Potential sources of bias were most pronounced in the blinding of participants and personnel, and outcomes in the randomized studies.…”
Section: Resultsmentioning
confidence: 99%
“…Full‐text review of these 624 articles was conducted and a total of 71 articles were selected for inclusion (Figure 1). 5,6,8,16‐82 Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Figure 2A and B). Potential sources of bias were most pronounced in the blinding of participants and personnel, and outcomes in the randomized studies.…”
Section: Resultsmentioning
confidence: 99%
“…49 Given the uncertain risk of bleeding with nonselective NSAIDs, the benefits of COX-2–specific inhibitors in terms of analgesic efficacy and platelet sparing effects, even at supra-therapeutic plasma levels, 19 are noteworthy and have been the focus of a recent meta-analysis 21 and demonstrated in five randomized controlled trials. 4,22,23,50,51 Celecoxib is an ideal analgesic for tonsillectomy because its oral suspension formulation can be administered both preoperatively and postoperatively in a twice-daily dosing schedule with a low parental burden for analgesia administration 52 and as part of a multimodal analgesic regimen after discharge. In adults, selective COX-2 inhibition is a recognized way to reliably reduce antiplatelet effects and bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies report that NSAIDs reduce dynamic pain with movement, 60 and celecoxib, beyond its effectiveness as a pre-emptive analgesic, can decrease dynamic pain with swallowing 4,61 and allows for a faster return to normal diet and activity after tonsillectomy compared with placebo 23 or acetaminophen. 22 This facilitates oral fluid and analgesic intake and may reduce the risk of postoperative hospital visits for dehydration and pain crises. 4,62 Although evidence for respiratory depression was not measured, our results support celecoxib as part of a multimodal opioid-sparing analgesic approach 7,23 to lower the risk of perioperative respiratory adverse events after tonsillectomy, 4 with opioid-induced respiratory depression being a particular concern in patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report CSF pharmacokinetics for three selective COX-2 inhibitors (celecoxib, valdecoxib, and rofecoxib), demonstrate analgesic hysteresis associated with these drugs and suggest that CSF concentration can explain, in part, the temporal delay observed for analgesic effect. Celecoxib use remains limited in children 24,26,27 and an understanding of pharmacokinetic-pharmacodynamic relationships can drive future investigation. Quantification of the temporal relationship between plasma and CSF concentration is rarely reported, yet is useful in order to interpret differences in effect onset, offset and to better identify analgesic target concentrations.…”
Section: Cox-2 Csf Simulationsmentioning
confidence: 99%